Star Projective and Star Injective Hv-Modules - A. Mortazavi; Bijan Davvaz (IndoMS, 2018)
In this paper, we introduce the concepts of product and directsum, star projective and star injective in H_v-modules. Weinvestigate generalizations of some notions in homological algebrato prove the five lemma and star projective and star injectivetheorems in H_v-modules. We determine equivalent conditions for split sequences in H_v-modules and present some related results.